2015
DOI: 10.1111/jcom.12201
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Pornography Consumption and Actual Acts of Sexual Aggression in General Population Studies

Abstract: Whether pornography consumption is a reliable correlate of sexually aggressive behavior continues to be debated. Meta-analyses of experimental studies have found effects on aggressive behavior and attitudes. That pornography consumption correlates with aggressive attitudes in naturalistic studies has also been found. Yet, no meta-analysis has addressed the question motivating this body of work: Is pornography consumption correlated with committing actual acts of sexual aggression? 22 studies from 7 different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
154
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(171 citation statements)
references
References 67 publications
12
154
0
5
Order By: Relevance
“…Thus, due to the content of popular pornography (Barron & Kimmel, 2000;Bridges et al, 2010;Gossett & Byrne, 2002;Klaassen & Peter, 2015;Makin & Morczek, 2015), consistently consuming such objectifying and sexually aggressive media could begin a process by which individuals view women as sexual objects and violence toward women as normative. This process could explain why a recent meta-analysis revealed that viewing pornography was positively associated with real-life sexual aggression (Wright, Tokunaga, & Kraus, 2016). However, given the aggressive and often disturbing content of popular Internet pornography, there is a need to evaluate differences in women (and not just men) who do or do not use Internet pornography.…”
Section: Sexual Socialization Of Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, due to the content of popular pornography (Barron & Kimmel, 2000;Bridges et al, 2010;Gossett & Byrne, 2002;Klaassen & Peter, 2015;Makin & Morczek, 2015), consistently consuming such objectifying and sexually aggressive media could begin a process by which individuals view women as sexual objects and violence toward women as normative. This process could explain why a recent meta-analysis revealed that viewing pornography was positively associated with real-life sexual aggression (Wright, Tokunaga, & Kraus, 2016). However, given the aggressive and often disturbing content of popular Internet pornography, there is a need to evaluate differences in women (and not just men) who do or do not use Internet pornography.…”
Section: Sexual Socialization Of Womenmentioning
confidence: 99%
“…Furthermore, prolonged exposure to both violent and nonviolent pornography decreased sensitivity toward victims of sexual violence, increased men's belief in their own propensity for forcing particular sex acts on reluctant female partners, and increased men's belief that they are capable of committing rape. Therefore, it is not surprising that across 22 studies worldwide, pornography use (both offline and online) is positively associated with actual acts of sexual aggression (Wright et al, 2016). After the advent of high-speed Internet, Sabina et al (2008) found that boys below the age of 18 who had repeated exposure to pictures of sexual violence were more likely to view acts of sexual aggression positively.…”
Section: Pornography Use and Attitudes Toward Women And Sexual Aggresmentioning
confidence: 99%
“…Associations were stronger for verbal than physical sexual aggression, although both were significant. The general pattern of results suggested that violent content may be an exacerbating factor (Wright, Tokunaga, & Kraus, 2015).…”
Section: Adolescents and Potential Harms From Internet Pornographymentioning
confidence: 81%
“…19 The results are the same in correlational, cross-sectional, experimental, and longitudinal studies: pornography use and acts of sexual aggression are directly connected. 20 The more men view pornography, the more they think that women are lesser creatures who they can dominate. 21 Pornography use increases the likelihood that a man will commit sexual violence against a woman, particularly if the man has other risk factors for committing sexual violence like being impulsive, and if his use of pornography is frequent.…”
Section: The Impact: Sexual Dysfunctionmentioning
confidence: 99%